Delphi consensus methodology to gauge expert perspectives on smoking prevention, cessation and harm reduction in Italy - Caponnetto, Pasquale; Contursi, Vincenzo; Fedele, Francesco; Lugoboni, Fabio; Novo, Salvatore (Frontiers in Psychiatry, 2025)
The role of smoke-free alternatives to cigarettes for tobacco harm reduction remains controversial. This study was conducted to understand the perspectives of a panel of Italian experts on this topic. Using Delphi consensus methodology, expert opinions on the use of smoke-free alternatives, tobacco harm reduction and anti-smoking legislation were gathered and analyzed. In July 2022, a Scientific Committee, including five members, proposed 38 statements spanning three areas: (1) harm from tobacco smoking and strategies for harm reduction; (2) smoke-free alternatives to cigarettes; and (3) anti-smoking legislation. Between August and November 2022, the Expert Panel, including members of the Scientific Committee and 15 other key opinion leaders, voted on the statements in two rounds. Consensus was achieved on 24 of 38 statements. The results emphasized the persistent national health threat posed by tobacco smoking in Italy, with a smoking prevalence of 20–24% between 2007 and 2022. Emphasizing harm reduction as a pivotal public healthcare strategy, the Expert Panel agreed on 10 statements related to smoke-free alternatives, but underlined the need for further research despite promising initial findings. The Expert Panel also reached consensus on six statements regarding anti-smoking legislation, stressing the importance of crafting and upholding rigorous anti-smoking laws that are consistent with World Health Organization guidelines. This pioneering Delphi consensus statement illuminates the complicated debate regarding the role of smoke-free alternatives for tobacco harm reduction in Italy. The findings highlight the evolving nature and advocate the need for ongoing discussions and further research on this important issue.